Soil fertility and land sustainability in Usangu Basin-Tanzania. Issue 8 (August 2021) - Mng'ong'o, Marco; Munishi, Linus K.; Blake, William; Comber, Sean; Hutchinson, Thomas H.; Ndakidemi, Patrick A.
Abstract: Soil fertility determines crop growth, productivity and consequently determines land productivity and sustainability. Continuous crop production exploits plant nutrients from soils leading to plant nutrient imbalance, thus affecting soil productivity. This study was conducted to monitor soil fertility status in soils of Usangu agro-ecosystem to establish management strategies. To assess soil fertility status in Usangu agro-ecosystem in Southern Highland Tanzania; 0–30 cm depth soil samples were taken for organic carbon, soil pH, N, P, Ca, K, Mg, S, Al, and micronutrients such as Zn, Mn, Cu, Fe, and Cr analyses by various established standard analytical methods. The results indicated most micronutrients were available in the deficient amount in many studied sites except for Fe and Mn, which were observed to be above optimum requirement. Based on critical levels established in other areas, 90 % of the soils were ranked as N, P, K, and Mg deficient. The micronutrients (Cu, Fe, and Zn) were inadequate in all soils resulting in limited crop growth and productivity. A high concentration of trace metals was detected in agricultural soils, this might affect plant nutrients availability and leading to environmental contamination affecting land productivity and sustainability. The study found that Usangu agro-ecosystem has deprived of soil fertility leading to poor crop growth and productivity. The authors recommend the addition of supplemental materials rich in plant nutrients such as inorganic fertilizer, manure, crop residues, and treated wastes to improve soil fertility for improved productivity and land sustainability. Abstract : Plant nutrients; Paddy wetlands; Trace metals; Soil fertility; Land sustainability.